2019
DOI: 10.1021/acs.jafc.9b01757
|View full text |Cite
|
Sign up to set email alerts
|

An Immunoaffinity Purification Method for the Simultaneous Analysis of Triclocarban and Triclosan in Foodstuffs by Liquid Chromatography Tandem Mass Spectrometry

Abstract: Triclocarban (TCC) and triclosan (TCS) have been simultaneously detected in five kinds of foodstuffs using an immunoaffinity purification method coupled with ultrahigh-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) for the first time. Two highly specific monoclonal antibodies against TCC and TCS were produced and coupled to N-hydroxysuccinimide-activated Sepharose 6B gel to prepare the immunosorbent. Under the optimal conditions, mean recoveries from spiked samples by the IAC-UHPLC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In a recent study by Azzouz et al [20], TCS residues were not detected in 13 different cereal-based foods (cookies, corn flakes, macaroni, muesli with fruit, multiseed bread, noodles, rice, sesame reganus, spaghetti, tortellini with cheese, wheat flour, wheat tortillas, and white bread) that were purchased from several shops and supermarkets in Spain. However, in another study by Yao et al [19], TCS residues were found in three raw chicken eggs (maximum = 6.7 ng/g), but not in samples of beer, soda, chicken meat, or cherries purchased at supermarkets in China. The authors suggested that the eggshells may have been indirectly contaminated at the supermarkets by employees using products (e.g., sponges or wipes) containing TCS to clean food preparation surfaces.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…In a recent study by Azzouz et al [20], TCS residues were not detected in 13 different cereal-based foods (cookies, corn flakes, macaroni, muesli with fruit, multiseed bread, noodles, rice, sesame reganus, spaghetti, tortellini with cheese, wheat flour, wheat tortillas, and white bread) that were purchased from several shops and supermarkets in Spain. However, in another study by Yao et al [19], TCS residues were found in three raw chicken eggs (maximum = 6.7 ng/g), but not in samples of beer, soda, chicken meat, or cherries purchased at supermarkets in China. The authors suggested that the eggshells may have been indirectly contaminated at the supermarkets by employees using products (e.g., sponges or wipes) containing TCS to clean food preparation surfaces.…”
Section: Discussionmentioning
confidence: 84%
“…TCS is not known to be incorporated into any food packaging materials [17], but this chemical has been used in a variety of consumer goods such as personal care products and kitchenware [14][15][16][17]. Only a few studies in the literature have quantified the concentrations of TCS residues in any foodstuffs, globally [18][19][20]. In a recent study by Azzouz et al [20], TCS residues were not detected in 13 different cereal-based foods (cookies, corn flakes, macaroni, muesli with fruit, multiseed bread, noodles, rice, sesame reganus, spaghetti, tortellini with cheese, wheat flour, wheat tortillas, and white bread) that were purchased from several shops and supermarkets in Spain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations